Analyses of Early Medieval Stained Window Glass From the Monastery of Baume‐Les‐Messieurs (Jura, France). (4th December 2015) - Van Wersch, L.; Loisel, C.; Mathis, F.; Strivay, D.; Bully, S.
Abstract : The collection of early medieval window glass found in the abbey of Baume‐les‐Messieurs (Jura, France) is exceptional because it dates to the end of the eighth century, and due to the number of fragments as well as their state of conservation. Different colours and forms have been identified. These pieces are a rare opportunity to address the glass craft, its recipes and techniques for a phase of its history that has remained little known. Analyses in PIXE–PIGE prove that, in addition to fragments from two soda glass items, the pieces are made from wood‐ash glass. Most of them probably came from the same production and the raw material is present in the region. At this early stage of wood‐ash glass production, the glassmakers had mastered the glass as well as the colour processes.